Nutritional deficiencies in italian pumpkin: characterization of symptoms, growth and mineral composition (Research, Society and Development, 2020)
Objective: to characterize the visual symptoms of simple and multiple deficiencies in Italian squash, growth parameters, and the mineral composition of the leaves grown in the nutrient solution. Material and Methods: The experiment was carried out in a greenhouse at the Department of Soil Science at UFLA, Lavras, MG. The statistical design used was the DIC with eleven treatments and three replications, in a nutrient solution based on the Hoagland & Arnon solution. The treatments were: complete nutrient solution (control), nutrient solutions with the individual omission of K, Ca, Mg, B, Mn, and Zn and multiple omissions of BZn, CaB, MnMg, and KZn. The plants were selected according to the size uniformity of the aerial part and roots and then, individualized in plastic pots with a capacity of eight liters, thus constituting each pot as an experimental plot. After the manifestation of visual deficiency symptoms, the treatment plants were harvested and the dry matter was subsequently collected and chemical analysis of the plants was performed. Results: The vestments analyzed for multiple nutritional deficiencies in Italian pumpkin have statistical differences between them. Conclusion: Multiple omissions CaB, BZn, and MgMn in nutrient solution result in morphological changes, translated into characteristic symptoms of deficiency. Deficiency symptoms were initially characteristic of each nutrient (with the exception of Zn and Mn), with the absence of nutrients in the solution, regardless of whether they are isolated or associated with another. Simple and multiple omissions affect the parameters of growth, dry matter production, levels, and nutritional accumulations of Italian pumpkin cv. Caserta.